Using multiple sources of characters to delimit species in the genus Crataegus (Rosaceae): the case of the Crataegus rosei complex. Issue 2 (3rd March 2016) - Piedra-malagón, Eva M.; Albarrán-lara, Ana Luisa; Rull, Juan; Piñero, Daniel; Sosa, Victoria
Abstract : The aim of this study was to delimit the taxa of the Crataegus rosei complex using an integrative approach that incorporates a suite of molecular (cpDNA and nuclear microsatellite markers), morphological, and geometric morphometric characters. One hundred and ten plants from 19 populations that encompass the entire distribution range of the species complex were collected and examined along with herbarium specimens. Parsimony and Bayesian inference analyses were run using morphological, molecular, and both the morphological and molecular data sets combined. Analyses to determine genetic structure based on microsatellite data and multivariate analyses incorporating geometric morphometrics were also done to identify differences in leaf shape. The results supported the recognition of two taxa: C. rosei with high levels of gene flow among its populations, remarkable morphological variation and a wide distribution range and C. rosei var. amoena, composed of a few isolated populations in the high elevation location of Cerro Potosí; a new specific epithet will be decided for the latter in accordance with the International Code of Nomenclature for algae, fungi, and plants.